PENGARUH PENGGUNAAN METODE PEMBELAJARAN MEDIA TRAINER SIMULATOR SISTEM STARTER SEPEDA MOTOR TERHADAP HASIL BELAJAR SISWA KELAS XI TSM SMKN 1 BONJOL - Putri, Riska Dwi; Andrizal, Andrizal; Rifdarmon, Rifdarmon; Saputra, Hendra Dani (Ensiklopedia of Journal, 2025)
Abstract: This study aims to analyze the influence of simulator trainer media on the learning outcomes of the motorcycle starter system compared to conventional lecture methods. Using a quantitative experiment method with a one group pretest-posttest design, the study involved 25 students in class XI TSM in the even semester of the 2024/2025 school year at SMKN 1 Bonjol. Data were collected through validated multiple-choice objective tests: 20 items for the pretest and 30 items for the posttest. Data analysis was conducted using the paired sample t-test. The results showed a significant increase from the average pretest of 68.8 to 83.28 in the posttest after the implementation of the simulator media trainer. The statistical test obtained a t-count of 9,438 > t-table of 2,064 with an influence rate of 21%, showing a significant difference in α = 0.05. It was concluded that the simulator trainer media can improve student learning outcomes on motorcycle starter system materials, providing a more concrete and interactive learning experience than conventional lecture methods.Keywords:  trainer simulator, learning outcomes, starter system, motorcycle, technical education.